Prinsip Suku Betawi Sebagai Inspirasi Utama Penciptaan Karya Tari Ngasosi - Kusumaningtyas, Aryati Dewi (TAMUMATRA, 2024)
A principle is something that is inherent and its truth is the basic principle for thinking and acting. The Ngasosi dance work is a new dance performance presented in pairs, which departs from the habits of Betawi people's lives. This research was carried out using qualitative methods, namely by explaining in detail the inspirational ideas and forms of presentation with a background of creativity carried out by choreographers in developing traditional Betawi dance, as well as expanding character education. This research uses primary and secondary data sources. The primary data source is interview notes, the researcher's secondary data source was obtained through literature studies in the form of books, scientific journals that support research, and photo documentation of variations in dance movements, fashion, make-up, props and musical scores. The resulting understanding is that this dance depicts a father and son who carry out the principles of life of the Betawi people, namely the Koran, prayer, silat which are applied in everyday life, where the principles of life of the Betawi people must be remembered from an early age until adulthood so that they become good habits and obligations. which has always been passed down from generation to generation.